2018
DOI: 10.1016/j.cognition.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

The role of alternative salience in the derivation of scalar implicatures

Abstract: Comprehension can be enriched by considering what a speaker could have said but did not; namely, the alternative. For example, "Betty passed some of her exams" can be interpreted as "Betty passed some but not all of her exams". This enriched interpretation is an example of a scalar implicature. We consider whether the salience and use of the alternative are independent processes in the derivation of scalar implicatures or whether use is dependent on salience. Participants completed three sentence interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…Yet part of the developmental literature suggests that children have more trouble understanding scalar implicatures with quantifiers than ad hoc implicatures (Barner, Brooks, & Bale, ; Stiller, Goodman, & Frank, ), while in contrast Katsos () suggests they calculate both types of implicatures to the same extent. Finally, somewhat in opposition to previous studies, Rees and Bott () found lower rate of implicature readings for ad hoc expressions than for the quantifier some or numerals in a study using a structural priming paradigm. Therefore, despite intensive theoretical and experimental interest in these quantity implicatures for the past decades, the layout of numerals, quantifiers, and ad hoc scales remains unclear.…”
Section: Introductioncontrasting
confidence: 86%
“…Yet part of the developmental literature suggests that children have more trouble understanding scalar implicatures with quantifiers than ad hoc implicatures (Barner, Brooks, & Bale, ; Stiller, Goodman, & Frank, ), while in contrast Katsos () suggests they calculate both types of implicatures to the same extent. Finally, somewhat in opposition to previous studies, Rees and Bott () found lower rate of implicature readings for ad hoc expressions than for the quantifier some or numerals in a study using a structural priming paradigm. Therefore, despite intensive theoretical and experimental interest in these quantity implicatures for the past decades, the layout of numerals, quantifiers, and ad hoc scales remains unclear.…”
Section: Introductioncontrasting
confidence: 86%
“…The first is that representations used to generate scalar implicatures must take alternatives as part of their inputthat is, sentences that the speaker could have said but didn't, for example, sentences involving all instead of some, as Grice (1975) and many others have argued. Correspondingly, Rees and Bott (2015) showed that sentences involving the alternative prime enrichment just as much as sentences involving the enriched scalar expression, and more than sentences involving the unenriched scalar expression. This type of input, and corresponding priming effects, do not apply to the semantic representations described by B&P. The second difference is that implicature representations are applied optionally (or defeasible), as in the standard Gricean model, for example, in the case of comprehension, application of the implicature representation would be blocked if the speaker is not judged to have had sufficient knowledge to have uttered the stronger expression.…”
Section: Alice Rees and Lewis Bottmentioning
confidence: 98%
“…Structural priming, however, can be used to investigate representations used in pragmatics, as well as in semantics and syntax. Bott and Chemla (2016) and Rees and Bott (2015; find that scalar implicaturesthe prototypical pragmatic enrichment can be primed. For example, Bott and Chemla showed that sentences with enriched interpretations of some (some à some but not all) prime higher rates of enrichment in subsequent target sentences than sentences with basic some (where some takes its literal meaning; i.e., some and possibly all).…”
Section: Alice Rees and Lewis Bottmentioning
confidence: 98%
“…More recent formulations have complicated this question by pointing out that even if scalar implicatures are context dependent they may not necessarily always take extra time or processing resources (Degen & Tanenhaus, 2015; Politzer‐Ahles & Gwilliams, 2015), and that the derivation of a scalar inference is not a monolithic process, but is a process involving multiple intermediate steps, each of which might be rapid and effortful or might be slow and costly (Chemla & Singh, 2014a,b). Some recent research is beginning to make steps towards evaluating these more articulated kinds of scalar implicature processing models; for example, Rees and Bott (2018) use the psycholinguistic paradigm of structural priming to investigate the properties of a particular sub‐component of the scalar implicature derivation process, the determination of which alternatives are relevant in the context (e.g., whether or not all is a relevant alternative to some in the discourse).…”
Section: Scalar Implicatures: Linguistic and Psycholinguistic Questionsmentioning
confidence: 99%